Spatially Resolved Dynamics of Cobalt Color Centers in ZnO Nanowires. Issue 1 (20th November 2022) - Plass, Christian T.; Bonino, Valentina; Ritzer, Maurizio; Jäger, Lukas R.; Rey‐Bakaikoa, Vicente; Hafermann, Martin; Segura‐Ruiz, Jaime; Martínez‐Criado, Gema; Ronning, Carsten
Abstract: The dynamics of color centers, being a promising quantum technology, is strongly dependent on the local environment. A synergistic approach of X‐ray fluorescence analysis and X‐ray excited optical luminescence (XEOL) using a hard X‐ray nanoprobe is applied. The simultaneous acquisition provides insights into compositional and functional variations at the nanoscale demonstrating the extraordinary capabilities of these combined techniques. The findings on cobalt doped zinc oxide nanowires show an anticorrelation between the band edge emission of the zinc oxide host and the intra‐3d cobalt luminescence, indicating two competing recombination paths. Moreover, time‐resolved XEOL measurements reveal two exponential decays of the cobalt luminescence. The fast and newly observed one can be attributed to a recombination cascade within the cobalt atom, resulting from direct excitation. Thus, this opens a new fast timescale for potential devices based on cobalt color centers in ZnO nanowires in photonic circuits. Abstract : Zinc oxide nanowires are implanted with cobalt atoms to create color centers. These are investigated using temporally and spatially resolved X‐ray excited optical luminescence combined with X‐ray fluorescence. The results reveal an anticorrelation of band edge emission and cobalt luminescence, indicating competing recombination paths. Two exponential decays are found, with a new fast decay attributed to the direct excitation.